Influence of Probiotic Food on the Growth Performance and Survival Rate of Gold Fish (Carassius auratus) - V.K, Remya; C.S, Neethu; M S, Vinitha; V.S, Chithra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study was conducted at the Postgraduate Department of Zoology, Sree Narayana College, Nattika, Insia. Twenty juvenile goldfish were randomly placed in two groups: a control group (n = 10) and an experimental group (n = 10), and acclimatized in the laboratory for one week prior to the experiment. The control group were fed a basal diet of fish meal, soybean meal, wheat flour, and rice flour., while the experimental group were fed a combination of the basal diet and probiotic food (curd) at a dosage of 4 g per day. The fish were kept in aerated and dechlorinated freshwater at a temperature range of 20-25°C and a pH of 7.4, and fed once daily in the morning, over an 8-week period. Mean Initial weight (MIW) for the Control fishes was 2.18g while the Mean Final weights (MFW) for the Control fishes were 2.88g. The MIW for the Experimental fishes fed with probiotics was 2.73g while the MFW was 4.1g. Survival rate was 50% for the Control fishes and 100% for the Experimental fishes fed.